Analysis of WAN Network Reliability Based on Response Time and Downtime at the Faculty of Information Technology UKSW - Kevin; Indrastanti R. Widiasari (P3M Politeknik Negeri Bengkalis, 2025)
Wide Area Network reliability is crucial in supporting academic and administrative activities in higher education institutions. This study aims to evaluate the reliability of the WAN network at the Faculty of Information Technology, UKSW, using response time and Downtime as the main indicators. The research employed a quantitative descriptive approach by utilizing PRTG Network Monitor, Ping, and Zabbix to measure network performance. The results showed that the average response time was 104.31 ms, with a maximum response time of 614.0 ms. The total Downtime recorded was 22 hours and 42 minutes, with a network uptime percentage of 80.16%. These findings indicate that while the network remains operational, optimization is needed to reduce latency fluctuations and minimize Downtime. Recommendations include enhancing network infrastructure and implementing proactive monitoring strategies.